KEDUDUKAN KETETAPAN MPR DALAM TEORI DAN PRAKTIK KETATANEGARAAN DI INDONESIA - Nita Ariyani (Universitas Muhammadiyah Gresik, 2019)
The decree of the MPR was reviewed based on the theory of Von Stufentbau De Rechtsordnung (Theory of Hans Nawiasky) not including legislation but included in the category of Staatsgrundgesetz (Basic / State Rules) which is the basis for the formation of more laws and regulations low. If the MPR decree is classified into a type of legislation then it is the same as placing it too low because the MPR Decree is included in the Staatgrundgesetz category (Basic Rules / Principles of the State and He provisions of the People's Consultative Assembly in terms of constitutional practices in Indonesia remain included in the type and hierarchy of laws and regulations as referred to in Article 7 paragraph (1) of Law Number 12 Year 2011 concerning the Establishment of Legislation for reasons of practicality in constitutional practice even though the theory and juridical consequences (amendments to the 1945 Constitution specifically regarding the authority of the MPR) do not allow for the inclusion of the MPR Decree as a type of legislation. Because in theory the position of the MPR Decree is higher and is not a statutory regulation but constitutes the Basic Rules / Principles of the State and a juridical consequence that the MPR does not have the authority to set out the Broad Outlines and Guidelines of the State but only has the authority to amend and stipulate laws the state of 1945